Histological In Vivo Evaluation of Intense Pulsed Light Technology: Assessing the Safety on Oral Soft and Hard Tissues - Yaniv Mayer; Amit Shenhav; Amin Younis; Eran Gabay; Hadar Giladi Zigdon (MDPI AG, 2024)
Intense pulsed light (IPL) is used for aesthetic and therapeutic purposes. According to recent literature, utilizing IPL may boost upregulation of anti-inflammatory cytokines, and downregulation of pro-inflammatory cytokines. Concerns have been raised about potential thermal damage to the soft and hard tissues in the oral cavity. Therefore, the aim of this study was to determine the safety of using IPL of various intensities in the tissues of the oral cavity. Methods: Three adult pigs were included in the trial. The oral cavity was divided into four quadrants and projected with a wide range of IPL settings. Alveolar bone, buccal mucosa, and gingival tissue samples were taken immediately and after 24 h. In each animal, one quadrant of the jaw was left untreated and served as a control. All samples were processed and stained with H&E. Results: Clinical examination showed no evidence of changes in the integrity of the examined tissues. Histological examination of the different tissues did not demonstrate significant thermal damage or changes in the characterization of the cells compared to the control tissues. Conclusions: The use of IPL in the oral cavity is safe and does not negatively affect the tissues.